Nile perch and the transformation of Lake Victoria. Issue 2 (27th May 2016) - Taabu-Munyaho, A; Marshall, BE; Tomasson, T; Marteinsdottir, G
Abstract : The transformation of Lake Victoria that began in 1980 followed the population explosion of Nile perch Lates niloticus, causing the apparent extirpation of 500+ endemic haplochromine species and dramatic physico-chemical changes. Officially introduced in 1962–1963, but present earlier, the reasons for the long delay before its population exploded are discussed. The hypothesis that it occurred only after the haplochromine decline is evaluated, but haplochromines declined only after the Nile perch expansion began. The sudden eutrophication of the lake was attributed to Nile perch, but evidence of eutrophication from 1950 onwards led some researchers to conclude that it was the result of climatic changes. We conclude that the haplochromine destruction disrupted the complex food webs that existed prior to the upsurge of Nile perch. The depletion of fish biomass by Nile perch may have been the source of extra phosphorus responsible for the eutrophication of the lake. After the Nile perch explosion in 1980 the fish population came to be dominated by only three species, but fisheries productivity increased at least 10-fold. Fishing has caused demographic changes in Nile perch, which may have allowed some haplochromine species to recover. The condition of the lake appears to have stabilised since 2000, partly because the fish biomass has risen to at least 2 × 10 6 t, replacing the 'lost' biomass and restoring some ecosystem functioning.